PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Pridata Geni Putri (Departemen Matematika, 2018)
Mathematical communication ability is one of the aspects that determines students’ success in achieving the goals of learning mathematics. However, in reality found that students’ mathematical communication ability in class VIII SMP Negeri 31 Padang were still low. The method that can be applied to improve students’ mathematical communication ability is by applying Realistic Mathematic Education (RME) approach. The purpose of this study is to know whether students’ mathematical communication ability who learned by using RME approach is better than those who learned by using scientific approach and to describe the development of students’ mathematical communication ability who learned by using RME approach in class VIII SMPN 31 Padang. This study was a combination between quasi experimental and descriptive study with static group design. Based on the result of data analysis, henced concluded students’ mathematical communication ability who learned by using RME approach is better than those who learned by using scientific approach.Keywords – mathematical communication ability ,realistic mathematic education approach, scientific approach.